Branch River flows toward the Place - Branch Cultural Historical Association (2008)
Branch River, known locally as the River, flows fourteen miles from its headwaters and branches at its mouth in the heart of Branch. Oral tradition has it that Thomas Nash was lured to Branch partly by salmon in the River. Today, Branch River is a licensed river popular among local and visiting anglers.